Distribution of Trauma Deaths in a Province of Korea: Is “Trimodal” Distribution Relevant Today? - Hwang, Kyungjin; Jung, Kyoungwon; Kwon, Junsik; Moon, Jonghwan; Heo, Yunjung; Lee, John Cook-Jong; Huh, Yo (Yonsei medical journal, 2020)
This study was designed to provide a basis for building a master plan for a regional trauma system by analyzing the distribution of trauma deaths in the most populous province in Korea. We investigated the time distribution to death for trauma patients who died between January and December 2017. The time distribution to death was categorized into four groups (within a day, within a week, within a month, and over a month). Additionally, the distribution of deaths within 24 hours was further analyzed. We also reviewed the distribution of deaths according to the cause of death and mechanism of injury. Of the 1546 trauma deaths, 328 cases were included in the final study population. Patients who died within a day were the most prevalent (40.9%). Of those who died within a day, the cases within an hour accounted for 40.3% of the highest proportion. The majority of trauma deaths within 4 hours were caused by traffic-related accidents (60.4%). The deaths caused by bleeding and central nervous system injuries accounted for most (70.1%) of the early deaths, whereas multi-organ dysfunction syndrome/sepsis had the highest ratio (69.7%) in the late deaths. Statistically significant differences were found in time distribution according to the mechanism of injury and cause of death ( <0.001). The distribution of overall timing of death was shown to follow a bimodal pattern rather than a trimodal model in Korea. Based on our findings, a suitable and modified trauma system must be developed.